Impact of E-Business on Business Association - Sandip U. Deshmukh (International Journal of Engineering and Management Research, 2019)
The said research paper involves a study of the impact of Electronic Commerce on Business. The research study has highlighted the Management Information Systems, Finance and Accounting, Marketing and Computer Sciences of E-Commerce on Business. E-commerce is a way of conducting business over the Internet. Though it is a relatively new concept, it has the potential to alter the traditional form of economic activities. Already it affects such large sectors as communications, finance and retail trade and holds promises in areas such as education, health and government. The largest effects may be associated not with many of the impacts that command the most attention but with less visible, but potentially more pervasive, effects on routine business activities. The integration of Electronic Commerce and Business will bring a renaissance in marketing function. As it present opportunities to get close to the customer to bring the customer inside the company, to explore new product ideas and pretest them against real customers.